2022
DOI: 10.3389/fmed.2022.876411
|View full text |Cite
|
Sign up to set email alerts
|

Twin Growth Discordance and Risk of Postpartum Hemorrhage: A Retrospective Cohort Study

Abstract: BackgroundIn recent years, the incidence of postpartum hemorrhage has increased globally. Multiple pregnancies and cesarean sections are well-known risk factors for postpartum hemorrhage. No studies have evaluated the associations between fetal growth anomalies and postpartum hemorrhage in women with twin pregnancies undergoing cesarean section. This study aimed to identify the relationship between fetal growth anomalies and postpartum hemorrhage in women with twin pregnancies undergoing cesarean section.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This association was especially apparent in patients with twin pregnancies complicated by FGR and sFGR, although these complications were not predictive of PPH. The authors have also found a stronger correlation between birthweight discordance and PPH in dichorionic twin pregnancies [30]. Another disorder associated with increased EFWd in early pregnancy is placenta previa.…”
Section: Maternal Morbidity In Pregnancies Complicated By Increased Efwdmentioning
confidence: 78%
See 1 more Smart Citation
“…This association was especially apparent in patients with twin pregnancies complicated by FGR and sFGR, although these complications were not predictive of PPH. The authors have also found a stronger correlation between birthweight discordance and PPH in dichorionic twin pregnancies [30]. Another disorder associated with increased EFWd in early pregnancy is placenta previa.…”
Section: Maternal Morbidity In Pregnancies Complicated By Increased Efwdmentioning
confidence: 78%
“…Apart from the risk of hypertensive disorders that is rooted in the pathogenesis of sFGR, increased birthweight discordance (≥ 20%) is also associated with a higher incidence of PPH (postpartum hemorrhage). In a study by Cao et al [30], a correlation was found between increased birthweight discordance and the incidence of PPH ≥ 1000 mL [OR 1.62 (1.05-2.51)] and PPH requiring invasive treatment [OR 1.62 (1.00-2.63)]. This association was especially apparent in patients with twin pregnancies complicated by FGR and sFGR, although these complications were not predictive of PPH.…”
Section: Maternal Morbidity In Pregnancies Complicated By Increased Efwdmentioning
confidence: 98%
“…In recent years, with the development of assisted reproductive technology and the use of ovulation-promoting drugs, the incidence of twin pregnancy has increased yearly. Twin pregnancy is susceptible to PPH due to uterine overdistension and myofibrillar hyperextension, which affects myofibrillar retraction, leading to weak uterine contractions in the postpartum period, which affects complete placental abruption and closure of blood sinuses at the abruption surface of the placenta [ 18 , 19 ]. In addition, twin fetuses have a large placental area, richer blood flow, more bleeding from small uterine arteries, and vein dissections during placental abruption, and are prone to complications of hypertensive disorders of pregnancy (especially sPE), amniotic fluid, placenta previa, and intrahepatic cholestasis in pregnancy, which increase the incidence of PPH in twin pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates, the articles were screened according to the inclusion and exclusion criteria yielding 398 for full-text review. Finally, 21 studies involving 23,330 pregnant patients met the eligibility criteria and were included in this study (4,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). The PRISMA ow chart (Figure S1) illustrates the details of the study selection process.…”
Section: Study Selectionmentioning
confidence: 99%